ANALISIS KELAYAKAN USAHA PEMASARAN BIBIT BUAH (Studi Kasus Pada CV. Flora Chania di Kecamatan Palaran Kota Samarinda) (The Feasibility Analysis of Marketing Business of Fruit Seedling (Case Study at the CV. Flora Chania in Palaran Subcity, Samarinda City)) - FADHILLAH KUSUMA RAHAYU; SYARIFAH AIDA (Universitas Mulawarman (University of Mulawarman), 2021)
The purposes of this research were to determine the cost, revenue, and profit of fruit seedling marketing and the feasibility of marketing business of fruit seedling at the CV. Flora Chania in Palaran Subcity, Samarinda City. This research was conducted during 3 months from March to May 2019. The data were collected secondary data. The analysis included calculation of cost, revenue, profit, Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B/C Ratio), dan payback period. The research results showed an average operational cost of IDR248,945,720.00 year-1 or IDR20,745,477.00 month-1, an average revenue of IDR349,900,000.00 year-1 or IDR29,083,333.00 month-1 and the average income of IDR100,818,566.00 year-1 or IDR8,326,547.00 month-1. This research found the NPV value of IDR37,464,538.00 at a factor discount rate of 10%, IRR value of 4.6%, Net B/C Ratio value of 1.32, while the payback period of 1 year and 4 months. The results of this research indicate that based on an assessment of technical aspect, management and legal aspects, market and marketing aspects, and financial aspect, the marketing of fruit seedling is feasible to be developed.